2014
DOI: 10.5312/wjo.v5.i3.312
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis: Nuclear medicine state-of-the-art imaging

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease, which is associated with systemic and chronic inflammation of the joints, resulting in synovitis and pannus formation. For several decades, the assessment of RA has been limited to conventional radiography, assisting in the diagnosis and monitoring of disease. Nevertheless, conventional radiography has poor sensitivity in the detection of the inflammatory process that happens in the initial stages of RA. In the past years, new drugs that significantly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
0
19
0
4
Order By: Relevance
“…The cause is not known, but it is quite likely that the unique physiological and anatomical features of diarthrodial joints may render those targets for RA [1,2]. The normal synovial membrane comprises an intimal lining of two or three layers of fibroblast-like and macrophage-like synoviocytes embedded in a dense extracellular matrix.…”
Section: Introductionmentioning
confidence: 98%
“…The cause is not known, but it is quite likely that the unique physiological and anatomical features of diarthrodial joints may render those targets for RA [1,2]. The normal synovial membrane comprises an intimal lining of two or three layers of fibroblast-like and macrophage-like synoviocytes embedded in a dense extracellular matrix.…”
Section: Introductionmentioning
confidence: 98%
“…Although it can affect numerous tissues and organs, it primarily involves flexible joints (6) resulting in synovitis, pannus formation (7) and massive bone destruction with consequent inflammation, pain and disability (8), associated with higher mortality as compared to the general population (9,10 Similarly, Gong et al (13) reported that 0.01 µg/ml 99 Tc-MDP significantly inhibited RANKL-induced osteoclastogenesis with no cytotoxicity, and significantly abolished the appearance of multinucleated osteoclasts, inhibited the expression of the transcription factors c-Fos, nuclear factor of activated T cells and inflammatory factors, such as IL-6, TNF-α and IL-1β. Thus, 99 Tc-MDP has anti-osteoclastogenic activity on RANKL-induced osteoclast formation.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Molecular imaging has already been proven successful in noninvasive and early response monitoring but, in most cases, is not specific for arthritis at a molecular level (11,13). Fibroblast activation protein (FAP) is a cell surface-bound, type II transmembrane glycoprotein belonging to the family of serine prolyl oligopeptidases.…”
mentioning
confidence: 99%